The spatial and temporal components of functional connectivity in fragmented landscapes - Auffret, Alistair G. (Ambio, 2015)
Connectivity is key for understanding how ecological systems respond to the challenges of land-use change and habitat fragmentation. Structural and functional connectivity are both established concepts in ecology, but the temporal component of connectivity deserves more attention. Whereas functional connectivity is often associated with spatial patterns (spatial functional connectivity), temporal functional connectivity relates to the persistence of organisms in time, in the same place. Both temporal and spatial processes determine biodiversity responses to changes in landscape structure, and it is therefore necessary that all aspects of connectivity are considered together. In this perspective, we use a case study to outline why we believe that both the spatial and temporal components of functional connectivity are important for understanding biodiversity patterns in the present-day landscape, and how they can also help us to make better-informed decisions about conserving and restoring landscapes and improving resilience to future change.